High-performance work practices and hotel employee performance: The mediation of work engagement - Karatepe, Osman M. (International journal of hospitality management, 2013)
► Training, empowerment, and rewards are considered as the indicators of high-performance work practices predicting work engagement. ► Work engagement seems to have a stronger relationship with extra-role customer service than with job performance. ► Work engagement acts as a full mediator of the effects of high-performance work practices on job performance and extra-role customer service. This study proposes and tests a research model that investigates whether work engagement functions as a mediator of the effects of high-performance work practices (HPWPs) on job performance and extra-role customer service. These relationships were assessed through LISREL 8.30 using structural equation modeling (SEM). Data were obtained from full-time frontline hotel employees and their managers in the Poiana Brasov region in Romania. The results suggest that work engagement acts as a full mediator of the effects of HPWPs on job performance and extra-role customer service. Specifically, HPWPs, as manifested by frontline employees’ appraisal of training, empowerment, and rewards, enhance work engagement. Such HPWPs in turn trigger job performance and extra-role customer service. Implications of the results are discussed and avenues for future research are offered.